Delovanje Ivana Molka po odhodu iz uredništva "Prosvete" in nastanek odbora Demokratične akcije ter "Svobodne besede" - Božič Horvat, Andreja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The paper presents the work of American Slovene politician and editor Ivan Molek from 1944 to 1950. When in 1943 Molek's political views against Yugoslav liberation movement were not in agreement with the policy of the Slovene National Benefit Society, he came into conflict with the members of the Supreme board of the Society and in 1944 he resigned from his post at Prosveta, the gazette published by the SNPJ. After his withdrawal from Prosveta, Molek only occasionally contributed to the daily. In 1946 he protested to the thirteenth regular convention of the SNPJ against the decision that the Supreme board made in February 1944. Molek appeared in public again in 1948 when he, John Langerholc and Charles Pogorelec established a Committee for Democratic Action and issued a Declaration and a Program. They identified themselves as Slovene American democratic socialists and the bearers of the new social-democratic movement among the Slovene Americans. In January 1949 the Committee published the first issue of the monthly called Svobodna beseda. According to Molek, the Committee achieved its goal; the Slovene National Benefit Society did not continue to support Slovene American National Council. When in 1950 the monthly discontinued Molek with drew to private life.
Keywords: Molek, Ivan, 1882-1962; slovenski izseljenci; United States of America; ZDA